Lippia origanoides Essential Oil or Thymol in Combination with Fluconazole Produces Damage to Cells and Reverses the Azole-Resistant Phenotype of a Candida tropicalis Strain (2023)
ABSTRACT: Candida tropicalis is one of the most pathogenic species within the genus. Increased antifungal resistance has been reported, which is in part due to the organism's ability to form biofilms. In natural products derived from plants, such as essential oils (EOs) or their major components, there is significant potential to develop new antifungals or to both enhance the efficacy and reduce the toxicity of conventional antifungals. This study aimed to evaluate the effect of combining an EO of Lippia origanoides or thymol with fluconazole on an azole-resistant C. tropicalis strain. Synergism was observed in the combination of fluconazole with the EO and with thymol, and minimal inhibitory concentrations for fluconazole decreased at least 32-fold. As a consequence of the synergistic interactions, mitochondrial membrane potential was reduced, and mitochondrial superoxide production increased. Alteration in nuclear morphology, cell surface, and ultrastructure was also observed. In conclusion, the synergistic interaction between L. origanoides EO or thymol with fluconazole reverted the azole-resistant C. tropicalis phenotype. These findings suggest that L. origanoides EO or thymol alone, or in combination with fluconazole, have the potential for development as antifungal therapies for this yeast, including resistant strains.